TRADISI LISAN ADAT MANDAILING KAJIAN SEMIOTIK “MAKKOBAR” - Susi Novi Handayani Hasibuan,; Elly Prihasti Wuriyani,; Rosmawaty Harahap, (JOEL: Journal of Educational and Language Research, 2022)
Tradition is one of the habits passed down from generation to generation by a group of people based on developing cultural values. In this paper, the author aims to provide an understanding and description of the study of oral traditions owned by the Mandailing Tribe. The form of tradition discussed in this study is the Batak Mandailing Marhata-Hata Marriage Tradition: “Makkobar”. The methodology used is descriptive qualitative approach and data analysis method using content analysis method. The conclusion of this research is that in the Mandailing Batak community, the Marhata-hata Marriage Customary tradition has until now been believed to have benefits and it is believed that if you carry out this tradition, it will bring blessings. Mulak Ari's oral literature in the wedding ceremony was spoken at Jorong Paroman Bondar. Marhata hata is spoken by traditional leaders (hatobangon). Mulak Ari is the final part.